Photographs, Manzanar, 1942-43 (1942)
Photograph shows the Toda family posing by a car, with a barrack in the background; Henry Toda is holding a shovel. Inscription on back of photograph: "Henry Toda, Father, Honey, Daughter, Akira, Son, (____ )Toda, Mother, Roy, Son. Manzanar, CA, Sept. 1942".